Zucchelli's technique or tunnel technique with subepithelial connective tissue graft for treatment of multiple gingival recessions - Bherwani, Chanchal; Kulloli, Anita; Kathariya, Rahul; Shetty, Sharath; Agrawal, Priyanka; Gujar, Dnyaneshwari; Desai, Ankit (Journal of the International Academy of Periodontology, 2014)
Gingival recession is both unpleasant and unesthetic. Meeting the esthetic and functional demands of patients with multiple gingival recessions remains a major therapeutic challenge. We compared the clinical effectiveness of Zucchelli's technique and tunnel technique with subepithelial connective tissue graft (SECTG) for multiple gingival recessions. Twenty systemically and periodontally healthy subjects having 75 recession defects (Miller's class I or II, 39 test and 36 control sites) were included. After initial nonsurgical therapy, test sites were treated with Zucchelli's technique and control sites with tunnel technique with SECTG. Plaque index, bleeding index, pocket depth, recession depth, clinical attachment level, and keratinized gingiva height were evaluated at baseline, 3 and 6 months post-surgery. The mean root coverage was 89.33% +/- 14.47% and 80.00% +/- 15.39% in the test and control groups respectively, with no significant difference between groups. Statistically significant root coverage was obtained for 82.50% +/- 23.72% and 71.40% +/- 20.93% of defects in the test and control groups, respectively. Zucchelli's technique is effective for the treatment of multiple adjacent recessions in terms of both root coverage and keratinized tissue gain, irrespective of the number of defects. Moreover, this technique does not require an additional surgical site as required in the gold standard SECTG.